Предмет: Алгебра,
автор: anudaanudari
(5+2x)^2-(2x-5)(2x+5) при x=-2
terikovramazan:
(5+2x)^2-(2x-5)(2x+5)=(2x+5)((2x+5-2х+5)=(2x+5)*10; (-2*2+5)*10=1*10=10;
Ответы
Автор ответа:
1
Ответ:
10
Объяснение:
(5+2(-2))²-(2(-2)-5)(2(-2)+5)= (5-4)²-(-4-5)(-4+5)= 1-(-9)=10
Автор ответа:
1
Ответ:
10
Объяснение:
Приложения:
Похожие вопросы
Предмет: Английский язык,
автор: печаенчаенаеа
Предмет: Русский язык,
автор: марк64
Предмет: Українська література,
автор: Віта1998
Предмет: Математика,
автор: Рапапра
Предмет: Математика,
автор: Annika1111